Validating a Scalable Approach to Microsurgery Education in Resource-Limited Countries - Darrach, Halley; Kneib, Cameron; Friedrich, Jeffrey; Inchauste, Suzanne; Mamo, Hellina Legesse; Chang, James (Journal of Reconstructive Microsurgery, 2025)
Microsurgery remains largely nonexistent in sub-Saharan Africa due to a lack of access to specialized training and microsurgical instruments. However, smartphones with magnification capabilities are globally widespread, even in low-resource nations. The use of smartphones as simulators for microsurgery training has been previously reported, but little is known with respect to skills acquisition over time.A cohort of Ethiopian plastic surgery attendees and residents participated in a microsurgery training workshop. Before and after the workshop, as well as 6 months afterward, participants were recorded performing a synthetic vessel repair using a smartphone for magnification. Video recordings were graded by four microsurgeons using the Stanford Microsurgery and Resident Training (SMaRT) scale, a validated instrument for assessing microsurgical skills.A total of 13 participants were surveyed and recorded. Overall microsurgical performance SMaRT scores significantly improved (2.05 vs. 2.72 on a five-point scale; p = 0.001) upon completion of the workshop, and continued to increase (3.05), but not significantly so (p = 0.201) 6 months afterward. However, improvements were maintained at 6 months. Significant improvement was noted in all SMaRT scale domains postworkshop and further significant improvement in instrument handling was noted at 6 months.Our findings suggest that smartphones can serve as valuable tools for microsurgery training in low-resource settings. Further research is warranted to evaluate the long-term impact of smartphone-based simulation training on skill acquisition and clinical outcomes in low-resource settings, but even in the short-term participants were able to demonstrate significant improvement, as well as maintenance to improvement of skill at 6 months follow-up.
Keywords: global surgery; microsurgery education; education